Penggunaan Jerk untuk Deteksi Dini Kerusakan Bantalan Gelinding dan Pemantauan Kondisi Pelumasan - Zainal Abidin; Budi Heryadi (Institute of Research and Community Outreach, Petra Christian University, 2011)
This paper describes the use of jerk signal, a signal obtained from differentiation of the acceleration signal with respect to time, for detecting the early damage of a bearing and bad lubrication conditions. The use of jerk signal is expected to result more sensitive detection than that obtain using acceleration signal. To prove this hypothesis, this paper shows the results of vibration measurement for needle bearings and taper roller bearings with variation of load level, types of bearing damage, and lubrication condition. Comparisons of acceleration and jerk signals are performed in both time domain, by comparing their RMS values, as well as in frequency domain, by comparing their spectrums. The results of the experiment show that the use of jerk signal can give a more sensitive result in detecting bearing damage than that produced using acceleration signal. Moreover, the use of jerk signal can lead to better results in detecting bad lubrication of rolling bearing than that obtain using Crest Factor (CF) value.